The Impact of the Increase in Tobacco and Electronic Cigarette Excise on State Revenue - Dea Retno Putri; Tony Sudirgo (Manunggal Halim Jaya, 2027)
State revenue is influenced by the contribution of tobacco excise. According to the APBN Kita publication by the Ministry of Finance (2026), Tobacco Excise (CHT) revenue in 2025 reached Rp216.9 trillion. This study was conducted with the aim of determining the effect of cigarette excise, electronic cigarette excise, the gross domestic product of the cigarette and tobacco industry, and the cigarette consumer price index on state revenue.This quantitative study uses 38 time series data points from 2016 to the second quarter of 2025. Data analysis was conducted using multiple linear regression with a natural logarithm transformation and then executed through the RStudio program. The empirical result demonstrates that the model escplains 44.34% (Adjusted R2) of the variance in state revenue research results indicate that the rates of tobacco excise, electronic cigarette excise, and cigarette CPI have a negative and significant effect on state revenue. Meanwhile, the GDP of the tobacco industry does not significantly affect state revenue. This study demonstrates that the government-imposed tariffs have led to a decrease in legal cigarette consumption, which ultimately reduces state revenue.